Predictors of Job Satisfaction and Commitment of University Employees: Basis for Intervention - Narbarte, Reuel E.; Balila, Jolly S.; Lascuna, Shirley J. (11th International Scholars Conference, 2017)
The Human Resource department in any institution would always determine how satisfied and committed the employees are in their organization. Thus, this study was conducted to examine the predictors of job satisfaction and commitment of employees in an academic institution. One hundred eighty (180) employees from academic support, general services, student services, and finance and auxiliary departments who hold managerial, professional, and support staff position were included in the study. Data from survey instruments developed by the Human Resource department were utilized to generate the results. The findings revealed that the employees have high level of job satisfaction and career commitment to their institution. Regression analysis indicates that the predictors of job satisfaction are: attracting high quality employees (β=.165), teamwork across departments (β=.356), salary and benefits of workers (β=.199). The total variance accounted for by these variables in job satisfaction is 52.9%. Further, the significant predictors of commitment are: retaining high quality employees (β=.181), years of service (β=-.110), and home and work balance (β=.149), which accounts for 14.2% of the variance in employee commitment. Based on these results, series of seminar/trainings and workshops were provided for employees.